Icaritin Enhancing Bone Formation Initiated by Sub-Microstructured Calcium Phosphate Ceramic for Critical Size Defect Repair - Peng, Haitao; Li, Jianxiao; Xu, Yanan; Lv, Guoyu (Frontiers in Materials, 2020)
Adequate bone regeneration has been difficult to achieve at critical-sized bone defects caused by disease. Bone tissue engineering using a combination of scaffolds and bioactive factors provides new hope for the treatment of this extreme condition. Icaritin, a herb-derived chemical, has shown its ability to enhance bone formation both in vitro and in vivo, and it has been found that sub-micron surface structure instructs bone formation in calcium phosphate ceramics (CaPs). We evaluated hereby the possibility to use a submicron surface structured CaP ceramic as the carrier of icaritin for bone regeneration. Icaritin, a herb-derived chemical, was loaded into a submicron surface structured porous calcium phosphate ceramic (Ø12.8x3mm) to get samples with 0, 10, 50, 250 and 1250 µg icaritin per CaP disc (M0, M10, M50, M250, M1250 groups, respectively). In vitro evaluation with the certain dosages correlated to those released from the samples showed a dose-dependent enhancement of osteogenic differentiation and mineralization of human bone marrow stromal cells (hBMSC) with the presence of osteogenic factors in the culture medium, indicating icaritin an osteopromotive factor. After an intramuscular implantation of the samples in dogs for 8 weeks a dose-dependent of bone formation in dogs was seen with enhanced bone formation at the dosage of 50 µg and 250 µg. To evaluate the in vivo osteogenic potentials of icaritin-containing CaP ceramic scaffolds in orthopedic site, a 12.8 mm calvarial defect model in rabbits was established. Micro-computed tomography (micro-CT) and histology results at weeks 4, 8 and 12 post-surgery showed more newly formed bone in M250 group, with correspondingly more new vessel ingrowth. The results presented herein suggested that being osteopromotive, icaritin could enhance bone formation initiated by sub-microstructured CaP ceramics and thus the combination of icaritin and osteoinductive CaP ceramics would generate a more powerful bone substitute for bone regeneration.